Human epidermal growth factor receptor 2 overexpression in endometrial carcinomas at a tertiary center in sub-Saharan Africa (2022)
Background: Endometrial cancer is the third most common gynecological malignancy, following cervical and ovarian malignancies. Prognosis among the women of African origin is, however, worse as they tend to have high grade tumors and late presentation. Close to 50% of high grade endometrial cancers show human epidermal growth factor receptor 2 (HER2) overexpression and may thus benefit from targeted treatment. Aims: This study aimed to determine the overexpression status of HER2 protein among the cases of endometrial carcinoma. Materials and Methods: All cases of histologically diagnosed endometrial carcinoma from January 2007 to December 2016 were retrieved from the files and records of department of pathology in our hospital. Cases were classified and graded according to the World Health Organization (2014 version) classification of endometrial carcinoma followed by immunohistochemical staining for HER2 overexpression. Results: There were a total of 51 cases of endometrial carcinoma that met the inclusion criteria during the study. The mean age of patients was 63 years. As a group, nonendometrioid carcinomas predominated (55%). The majority (70%) of cases showed high grade histological morphology. Positive Her2/Neu expression was seen in 11 cases (22%) of endometrial carcinoma. There was no statistically significant association between hormone expression status and age, histological variant, or grade. Conclusion: Endometrial carcinomas among Nigerian women are predominantly nonendometroid and high grade. HER2 overexpression was seen in a fifth of cases. Future studies should explore the response of targeted therapy among Nigerian patients showing HER2 overexpression.